Application of Indonesian Food Processing Recipes as an Android-based Learning Media for Students of the Culinary Study Program - Sulistiawikarsih Sulistiawikarsih (Randwick International of Education and Linguistics Science Journal, 2022)
Technological developments affect the role of an android itself. Now, all activities can be done with android. One of the obstacles in learning Indonesian food processing is the determination of a standard recipe that will be practiced. Based on this condition, the researchers made an application for Indonesian food processing recipe books for android-based students. The research process is carried out based on the Fish Bone Diagram, the testing method is the Blackbox Testing method. The testing phase of the application only focuses on the functionality of the application. Based on the conclusions, it is known from this research that it produces a responsive online application-based food recipe application, so that it can be accessed by users wherever they are as long as they are still connected to the internet, provide better information than similar services, and make it easier for users to determine the recipe menu for food to be served. Practiced.